Recent Patents on Abnormal Hydrodynamic Thrust Slider Bearings: Part II-the Second Mode of the Bearings - Zhang, Yongbin; Cheng, Huansheng; Wang, Junyan (Recent Patents on Mechanical Engineering, 2020)
Background: As a successive part, the paper introduces the second mode of abnormal hydrodynamic thrust slider bearings with divergent surface separations registered in the patents, where the boundary slippage is artificially designed both on the stationary surface in the inlet zone and on the whole moving surface. Objective: To introduce a second method for artificially designing the boundary slippage for the formation of abnormal hydrodynamic thrust slider bearings. Methods: The analytical results are presented for the introduced bearings. The performances of the bearings are demonstrated. Results: In appropriate operating conditions, the introduced bearings can have considerable loadcarrying capacities with low friction coefficients on the scales 10-3 or 10-4. With the weakening of the boundary slippage on the moving surface, the load-carrying capacities of the bearings are all increased, while the friction coefficients of the bearings are all reduced. Conclusion: When the boundary slippage is present both on the stationary surface in the bearing inlet zone and on the whole moving surface, abnormal hydrodynamic thrust slider bearings can be designed with the surface separation in the bearing inlet zone lower than that in the bearing outlet zone. The performances of these bearings are quite satisfactory.
Keywords: boundary slippage